Pengolahan Limbah Cair Industri Pulp Dan Kertas Dengan Metode Advanced Oxidation Process Berbasis Sulphate Radical (Sr-Aop) Menggunakan Katalis Nitrogen-Doped Three-Dimensional Carbon Framework (3D NCF) - Apriliani, Marissa; Saputra, Edy; Zultiniar, Zultiniar (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Wastewater of pulp and paper industry has low BOD5/COD ratio (average 0,3) while good biodegradability value was considered in the range over 0,5. These data indicate that lignin and its derivatives in the effluents exhibit slow degradation kinetics for conventional treatment process. There is an increasing interest in utilization of sulphate radical based advanced oxidation processes (SR-AOP) for destruction of slow degrading compounds. SR-AOP is based on the production of sulphate radicals as oxidizing agents. Sulphate radical can produce by activation of peroxymonosulfate. Metal free catalyst have been employed as the more effective activators for peroxymonosulfate to generate sulfate radical because the negative effect of leaching ions from heterogeneous metal catalyst can not fully neglected. Nitrogen doped three dimensional carbon framework (3D NCF) as metal free catalyst has been synthesized by annealing a zeolitic imidazolate framework (ZIF-67), followed by removing the cobalt metal. Physical properties were characterized by several techniques such as XRD. Effect the concentration of catalyst (0,1-0,4 g/L) was investigated in this research. Result indicating that 3D NCF exhibited remarkable degradation activity with the efficiency degradation of COD up to 88,22 % within 120 minutes at condition 0,4 g/L catalyst, 2,0 g/L PMS, 30oC and stirred constantly at 400 rpm. Keywords: advanced oxidation processes, metal free catalyst, nitrogen-doped three dimensional carbon, peroxymonosulfate, wastewater of pulp and paper